Why building participatory dashboards is key for sustainable food system transformation - Béné, Christophe; Chege, Christine Kiria; Even, Brice; Hernandez, Ricardo Alfonso; Lundy, Mark; Prager, Steven Dean; Wiegel, Jennifer (Frontiers Media, 2024)
In recent years, numerous examples of food system dashboards have been developed with the goal of offering users the opportunity to monitor or assess (their) national food systems. One of the many challenges faced by these initiatives has been to strike an acceptable balance between the complexity, local-specificity, and multi-sectoral nature of these food systems while also ensuring that the information remains accessible and usable for decision-makers. Perhaps even more critical, yet rarely discussed or implemented in most of the current food system dashboard initiatives, is the imperative of co-constructing these initiatives with local stakeholders. The case presented in this study puts participation at the center of the design and construction of a food systems’ monitoring dashboard. Using a replicable yet rigorous methodology, we demonstrate the feasibility of co-creating food system dashboards that integrate comprehensive and multi-sectoral inputs from national stakeholders while ensuring these dashboards are functional, evidence-based, and reflective of the country’s specific features. The approach is illustrated with the empirical cases of three pilot countries within the low-and middle-income countries group (Bangladesh, Ethiopia, and Honduras), where the methodology was tested between 2021 and 2022. We conclude by succinctly examining the ongoing challenges in constructing actionable food system dashboards.